FORMULASI SEDIAAN SABUN PADAT KOMBINASI EKSTRAK KULIT NANAS (Ananas comosus L.) DAN KULIT DURIAN (Durio zibethinus) TERHADAP Staphylococcus aureus: FORMULASI SEDIAAN SABUN PADAT KOMBINASI EKSTRAK KULIT NANAS (Ananas comosus L.) DAN KULIT DURIAN (Durio zibethinus) TERHADAP Staphylococcus aureus - Wahyu Tri Mulyani, Yuli; Sari, Novita; Nurjanah, Siti; Anasis, Annisa Mulia; Harissa, Nola (JFL : Jurnal Farmasi Lampung, 2024)
Staphylococcus aureus bacteria are bacteria that can cause infections. Prevention can be done by cleaning the body with soap. Soap is a skin cleansing preparation made from a saponification process between oil and organic or inorganic bases. Pineapple and durian peel contain active antibacterial compounds, namely alkaloids, flavonoids, saponins, and tannins. This study aims to determine the antibacterial activity of solid soap combined with pineapple peel and durian peel extracts against Staphylococcus aureus. The research method used was a laboratory experimental method with a solid soap formulation combining pineapple peel and durian peel extracts. Solid soap formulations are tested for bacteria using the hole/well method. The formulations used are F0 (soap base), F1 (0 pineapple peel extract and 4% durian peel), F2 (1% pineapple peel extract and 3% durian peel), F3 (2% pineapple peel extract and 2% durian peel), F4 (pineapple peel 3%, durian peel 1%), F5 (pineapple peel extract 4% and durian peel 0%), and a positive control (solid antibacterial bath soap brand x). A solid soap preparation has been made and has fulfilled the requirements for evaluating the quality of soap preparations, including organoleptic tests, homogeneity tests, pH tests, foam height tests, and stability tests. The results of tests on bacteria showed that the F0 inhibition zone was nonexistent, F1 was 9.72 mm, F2 was 11.31 mm, F3 was 11.73 mm, F4 was 12.15 mm, F5 was 10.34 mm, and the positive control was 14.18 mm. The conclusion of this study was that the best formulation with the largest zone of inhibition was at F3 of 13.73 mm with a strong inhibitory response to Staphylococcus aureus. Keyword: Ananas comosus, Antibacterial soap, Durio zibethinus, Staphylococcus aureus